2016
DOI: 10.1080/19443994.2015.1070761
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of Reactive Red 141 removal by heterogeneous photo–Fenton reaction using ZnFe2O4 oxide prepared by microwave irradiation

Abstract: A B S T R A C TA statistical optimization of Reactive Red 141 (RR141) removal by heterogeneous photoFenton reaction using ZnFe 2 O 4 particles was performed. ZnFe 2 O 4 oxide was synthesized by microwave-assisted solvothermal route and characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and N 2 adsorption-desorption isotherms. This material was used as a catalyst for the removal of RR141 dye from aqueous solution. Statistical optimization for the RR141 removal was performed using a 2 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…Stringhini et al 35 observed a total dye removal at 120 min of reaction using ZnAl 2 O 4 catalyst under UV irradiation, whereas Foletto et al 24 obtained total removal at 180 min using the same catalyst, but under sunlight. ZnFe 2 O 4 catalyst prepared by microwave irradiation showed 90% of dye removal at 60 min of reaction under visible light 36 . Therefore, the results obtained in this work demonstrate that the mesoporous Fe 2 O 3 -supported ZSM-5 zeolites are efficient catalysts for the removal of Reactive Red 141 dye from aqueous solution.…”
Section: Catalytic Evaluationmentioning
confidence: 98%
“…Stringhini et al 35 observed a total dye removal at 120 min of reaction using ZnAl 2 O 4 catalyst under UV irradiation, whereas Foletto et al 24 obtained total removal at 180 min using the same catalyst, but under sunlight. ZnFe 2 O 4 catalyst prepared by microwave irradiation showed 90% of dye removal at 60 min of reaction under visible light 36 . Therefore, the results obtained in this work demonstrate that the mesoporous Fe 2 O 3 -supported ZSM-5 zeolites are efficient catalysts for the removal of Reactive Red 141 dye from aqueous solution.…”
Section: Catalytic Evaluationmentioning
confidence: 98%
“…Para a avaliação fotocatalítica foram executados 15 testes reacionais em duplicata seguindo um planejamento experimental do tipo Box-Behnken explicitado pela Tabela 2 com três fatores (pH, concentração de catalisador e tempo de reação), cujos níveis foram retirados da literatura (Anchieta et al, 2016), sendo a variável dependente o rendimento percentual médio (R) do processo foto-Fenton, dado por Eq. (1).…”
Section: Identificação Composiçãounclassified
“…Nas últimas décadas, processos oxidativos avançados (POAs) têm recebido grande destaque por ser uma tecnologia emergente para a degradação de poluentes orgânicos em efluentes aquosos. Dentre os diversos tipos de POAs existentes [4], a reação heterogênea Fenton tem sido empregada com sucesso na degradação de diversos poluentes orgânicos [5][6][7]. A tecnologia Fenton consiste na combinação de peróxido de hidrogênio e cátions de ferro em um meio aquoso, produzindo radicais altamente reativos (HO • ) [8], levando à oxidação do poluente orgânico.…”
Section: Introductionunclassified